2022
DOI: 10.1101/2022.12.26.521927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse helpers ensure maternal-infant survival

Abstract: Parental care is required to ensure the health and survival of offspring. Caretaking in mammals is challenging as infants are largely helpless and require near-continual oversight over prolonged periods. Mouse pups in particular cannot thermoregulate, and will succumb to hypothermia unless kept warm by an adult caretaker or an insulating nest. Parents must balance caretaking behaviors with other activities important for survival such as regulating their own temperature and foraging for food or water, which nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…While standard maternal behavior tests (MBTs) were planned to begin on lactation day 2 (LD2), half of all dams' (8/16) litters had died by then. Instead, naturalistic MBTs (Carcea et al, 2021;Dvorkin and Shea, 2022;Schuster et al, 2023) were scored from footage obtained on LD1 in which all dams showed activity. Naturalistic MBT analysis showed that 7/8 kainic acid-treated dams failed to engage in any maternal behavior, resulting in the death of 100% of their litters by LD2.…”
Section: Lhb Kainic Acid Lesions Induced a Severe Maternal Neglect Ph...mentioning
confidence: 99%
See 2 more Smart Citations
“…While standard maternal behavior tests (MBTs) were planned to begin on lactation day 2 (LD2), half of all dams' (8/16) litters had died by then. Instead, naturalistic MBTs (Carcea et al, 2021;Dvorkin and Shea, 2022;Schuster et al, 2023) were scored from footage obtained on LD1 in which all dams showed activity. Naturalistic MBT analysis showed that 7/8 kainic acid-treated dams failed to engage in any maternal behavior, resulting in the death of 100% of their litters by LD2.…”
Section: Lhb Kainic Acid Lesions Induced a Severe Maternal Neglect Ph...mentioning
confidence: 99%
“…Notably, the only kainic acid-treated dam that performed maternal behavior at control levels (mouse X306) was later shown to have the same number of total surviving neurons as those from the saline-treated group (Figure 2A, B, Extended Figure 7-2). The only saline-treated dam that neglected her pups (Figure 1C-E) may have reflected the known baseline rate of neglect in mouse dams (Schuster et al, 2023), as her brain could not be assessed for possible accidental injection damage, since the brain tissue from 5 animals (2 saline-treated and 3 kainic acidtreated), including hers, was damaged during COVID-19 lab shut downs and so the subsequent histology was uninterpretable.…”
Section: Lesion Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent preprint by Schuster and colleagues suggests a way forward using continuous home-cage recording and DeepLabCut to gauge maternal presence in the nest. 13 Similarly, Winters and colleagues recently reported on the automation of the pup retrieval test. 14 My lab has also recently begun using a similar, albeit a simplistic, example of parental behavior automation.…”
mentioning
confidence: 96%
“…One of the strengths of automated behavior scoring is in identifying postures, for which automated approaches like DeepLabCut 4 can excel. A recent preprint by Schuster and colleagues suggests a way forward using continuous home‐cage recording and DeepLabCut to gauge maternal presence in the nest 13 . Similarly, Winters and colleagues recently reported on the automation of the pup retrieval test 14 .…”
mentioning
confidence: 99%